Effect of complex baking improver on prolonging freshness of bakery products with reduced salt content - Bilyk, Olena; Stabnikov, Victor; Vasheka, Oksana; Bondarenko, Yuliia; Kochubei-Lytvynenko, Oksana (My University, 2022)
The aim of research was to determine the effect of a complex baking improver on prolonging the freshness of bakery products with a reduced salt content using the principles of lean manufacturing. Sociological research on the requirements for the quality of bakery products was conducted. A composition of a complex improver "Mineral Freshness Plus” was developed and its optimal dosage was determined. The effects of the developed improver addition on the quality of bakery products with reduced salt content of 0.5% by weight of flour, and the effect on the processes of staling products during storage were studied. According to sociological studies the presence of ingredients of synthetic origin in bakery products and rapid loss of their freshness is undesirable for consumers. To meet the consumer demands, the use of the principles of lean manufacturing in bakery production is provided, which consists in reducing technological costs and losses due to application of the developed improver. A recipe for a complex baking improver Mineral Freshness Plus has been developed, which is designed to intensify the technological process, improve consumer properties and time for keeping the freshness of bakery products with low salt content of 0.5%. The composition of the improver includes food additives with Generally Recognized as Safe status. Addition of "Mineral Freshness Plus" improver in quality of 2.0% to flour weight extends freshness of bakery products. This is confirmed by the higher by 65.2–75.6% content of dextrins in the product with the improver comparштп with the control, the thinner subcrustal layer on 72 hours of products storage, and changes in the structure of the bread pulp, which consists of interspersed swollen and partially gelatinized grains of starch, wrapped in a continuous mass of coagulated proteins. The use of the developed improver "Mineral Freshness Plus” in the manufacture of bakery products ensures the high consumer demands.
Keywords: bakery; lean management; свіжість хлібобулочних виробів; поліпшувач комплексний; кафедра технології хлібопекарських і кондитерських виробів